Call for papers: Special issue: Crisis and New Social Movements across Europe: the Birth of a Critical European Civil Society? - Revista de Pensament i Anàlisi, Recerca (RECERCA. Revista de Pensament i Anàlisi, 2014)
In recent years, Europe has witnessed an emergence of political activism through the irruption of new social movements –15M or Occupy–, the birth of new political platforms –5 Stelle, Pirate Party, Zyrisa, X Party– and the emergence of new direct action groups such as Anonymous, anti-eviction movements and cooperatives, to name just a few (Castells, 2012; Mason 2012; Della Porta, 2013; Micó & Casero-Ripollés, 2013). In some countries, this activism has not just led to substantial pressure upon the traditional actors of representative democracy and governments, but also seemed to open opportunities for structural changes in context and procedures of policy making. One scenario is the recognition of citizen claims and initiatives to have a bigger say in governance, or a greater deal of political participation in relevant decision-making processes (Keane, 2009; Rosanvallon, 2008; Saward, 2010, Tormey, 2014). Another scenario is the development of alternative means of access to collective services and mutual help outside the sphere of the state – possibly in the tradition of older social economy experiences (Graeber, 2013). Both scenarios may be combined in some cases. How do we interpret the rise of ngos, social networking, mass protests, diy politics and other forms of sub-politics in terms of the scenarios and perspectives of a diverse civil society and its social movements?